No Difference in Two-Dimensional Kinematic Assessment of a 45-Degree Sidestep Cut Compared to Qualitative Assessment - Lauren Butler; Charles Wyatt; Alexa Martinez; Ashley Erdman; Eryn Milian; Dai Sugimoto; Alex Loewen; Jeffrey Fernandez; Kristin Hayden; Amie DeVerna; Kirsten Tulchin-Francis; Sophia Ulman (International Journal of Sports Physical Therapy)
# Background and Purpose